Rectal perforation after barium enema: A case report - Josiana de Oliveira Martins Duarte; Paula Maria Lobato Pestana Pereira; Ana Sofia Gonçalves Sobral; João Pedro Rosa deOliveira; Henrique José Barrelas Rita; José António deSousa e Costa (Clinical Case Reports, 2019)
Abstract Colorectal perforation after barium enema it is a rare complication, but has a high mortality rate. With the emergence of endoscopic examinations, barium enemas have fallen into disuse and doctors are less aware of its complications. This case is of the utmost importance as failure to recognize it could be fatal.